2005
DOI: 10.1074/jbc.m502406200
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Blockers of the Inhibition of Neuronal Nicotinic Acetylcholine Receptors by Amyloid β

Abstract: Alzheimer disease (AD) is characterized by accumulation of the neurotoxic amyloid ␤ peptide (A␤) and by the loss of cholinergic neurons and nicotinic acetylcholine receptors (nAChRs) throughout the brain. Direct inhibition of nAChRs by A␤ has also been suggested to contribute to cholinergic dysfunction in AD. In an effort to find ligands capable of blocking A␤-induced inhibition of nAChRs, we have screened a phage display library to identify peptides that bind to A␤. Using this approach, we identified a heptap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
53
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 35 publications
6
53
1
Order By: Relevance
“…Magdesian and colleagues [30] have demonstrated that A␤ binds at the interface between the acetylcholine and nicotine binding domains of the ␣7nAChR. Additionally, A␤-evoked Ca 2+ efflux from nerve terminals was not increased after coapplication of nicotine suggesting similar binding sites [31,32].…”
Section: Discussionmentioning
confidence: 96%
“…Magdesian and colleagues [30] have demonstrated that A␤ binds at the interface between the acetylcholine and nicotine binding domains of the ␣7nAChR. Additionally, A␤-evoked Ca 2+ efflux from nerve terminals was not increased after coapplication of nicotine suggesting similar binding sites [31,32].…”
Section: Discussionmentioning
confidence: 96%
“…The display of random peptides on filamentous bacteriophage has allowed the identification of peptides that bind specifically to a variety of targets, including A␤ (25,33,34). Peptides thus identified have been shown to act as agonists or antagonists of various receptors and to mimic the binding sites of physiological receptors (25).…”
Section: Discussionmentioning
confidence: 99%
“…The display of random peptides on filamentous bacteriophage has allowed the identification of peptides that bind specifically to a variety of targets, including A␤ (25,33,34). Peptides thus identified have been shown to act as agonists or antagonists of various receptors and to mimic the binding sites of physiological receptors (25). Using this approach, we have now identified a cysteine-linked heptapeptide (denoted cSP5) that binds to soluble A␤40/A␤42 and is homologous to the extracellular cysteine-rich domain (FzCRD) present in several members of the Fz family of Wnt receptors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations